The Evaluation of Implementation of Integrated Pest and Disease Control by Farmers of Food and Holticultural Corps in Banyuasin and Ogan Komering Ulu Timur - suparman SHK; Arsi; Bambang Gunawan; Abu Umayah; Yulia Pujiastuti; Harman Hamidson (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Reducing crop cultivation is providing ecological biota for plants through Integrated Pest Management (IPM). Farmers' problems regarding pests and diseases in Banyuasin and OKU Timur, especially for food crops and horticulture farmers. The purpose of this research is to evaluate the compliance of food crops and horticulture farmers in implementing safe and environmentally friendly IPM. Study on various fields of food and horticulture farmers in Banyuasin and Ogan Komering Ulu. The research method used is purposive sampling. Observation of Plant Pests and Diseases was completed directly in the field. Then determine the disease score in each sample plant. The parameters observed in this study are the behavior of farmers towards the decision-making process of using pesticides. Pest and disease intensity, and disease attack percentage were analyzed descriptively in the form of tables and graphs, as well as correlation analysis. The highest value of diversity of pests and diseases of food and horticultural crops based on the entire area of the observed land was found in a land area of 0.25 ha, which is the area that is often found in land for crop cultivation. The average age percentage of farmers in Banyuasin and OKU East is 40 to 50 years old. The average education of farmers in Banyuasin and OKU Timur is 24 farmers. The percentage and intensity of both horticultural and food crops in Banyuasin are good because only a few farmers get a score of 2 or 1. Cultivation techniques are land preparation, land sanitation, selection of resistant varieties, spacing, irrigation, crop rotation, intercropping, mulching, natural enemies of insects, and weeding.